Operational thresholds of urease-mediated microbial cementation: Multivariate optimization and field validation in ambient groundwater environments - Jiajian Bao; Wangqing Xu; Dongming Zhou (PLoS ONE, 2025)
Microbially induced calcium carbonate precipitation (MICP) provides a sustainable method for soil stabilization; however, its practical application is limited by rapid reaction kinetics that cause localized clogging and the reliance on energy-intensive environmental controls. This study develops a multivariate optimization framework for urease-inhibited MICP using N-(n-butyl)-thiophosphoric triamide (NBPT), with an emphasis on practical thresholds under ambient groundwater conditions. Five operational parameters—NBPT concentration, cementing solution concentration, bacteria-to-cement solution ratio, temperature, and pH—were systematically investigated through sand column tests and continuous urease activity monitoring. The results demonstrate that a low NBPT concentration of 0.1%, in conjunction with a 1:1 volumetric ratio of bacterial suspension to cementing solution, achieves effective biocementation while maintaining 93% of the unconfined compressive strength observed in inhibitor-free controls. Optimal performance was achieved at a cementing solution concentration of 1 mol/L, temperatures exceeding 20°C, and a neutral pH range of 7–8. The proposed thresholds bridge the critical gap between laboratory-optimized MICP and real-world environmental variability, providing directly implementable guidelines for sustainable geotechnical applications. This study advances NBPT-MICP as a cost-effective and environmentally compatible solution for sand stabilization in natural hydrochemical systems.